1972
DOI: 10.1159/000213990
|View full text |Cite
|
Sign up to set email alerts
|

Different Cross-Over Electrophoretic Mobility of Factor Friuli X and Coumarin-induced Abnormal Factor X

Abstract: Lyophilized or frozen plasmas with congenital deficiencies of factors II, VII, IX, or X, abnormal factor X (factor X Friuli) plasma, absorbed normal plasma, plasmas from patients treated with coumarin anticoagulants and normal plasma were studied in a crossover electrophoresis (electrosyneresis) system using an anti-factor X antiserum. A factor X band was present in plasmas with a deficiency of factors II, VII, and IX, in abnormal factor X plasma, and in normal plasma. No difference in the position of the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1974
1974
1976
1976

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Further more, it was demonstrated that the cross-over electrophoresis mobility of factor X Friuli is identical to that of normal factor X and is different from the mobility shown by the coumarin-induced abnormal factor X [13,16]. Finally, it was demonstrated that no PIVK.A (prothrombin inhibitor vi tamin K absence) type inhibitor is present in Friuli plasma [17].…”
mentioning
confidence: 99%
“…Further more, it was demonstrated that the cross-over electrophoresis mobility of factor X Friuli is identical to that of normal factor X and is different from the mobility shown by the coumarin-induced abnormal factor X [13,16]. Finally, it was demonstrated that no PIVK.A (prothrombin inhibitor vi tamin K absence) type inhibitor is present in Friuli plasma [17].…”
mentioning
confidence: 99%
“…Furthermore, no inhibitor or PIVKA-like substance was found in Friuli plasma [12]. Finally, it was shown that the abnormal factor X has the same cross-over electrophoretic mobility as normal factor X and a different one from the coumarin-induced abnormal factor X [11,15], The patients homozygote for the factor X Friuli coagulation disorder present a moderate bleeding tendency characterized mainly by easy bruis ing, menomethrorrhagias, épistaxis, bleeding after tooth extractions and after surgical procedures. Hemarthrosis was seen only in one patient after a trauma [4-6, 9, 13, 14].…”
mentioning
confidence: 99%
“…The condition is transmitted as an au tosomal incompletely recessive trait [10,18,21,24], The main feature of the defect consists in the presence of an abnormal factor X which may not or may be activated only very slowly by whole or partial tissue thromboplastin whereas it may still be normally activated by Russell's Viper venom [7][8][9]16]. It was also demonstrated that prothrombin is normal in Friuli patients both as activity and as antigen [13] and that no inhibitor is present [17,22], Immunologically, factor X Friuli behaves as normal factor X both in plasma and is different from coumarin-induced abnormal factor X [15,19,23],…”
mentioning
confidence: 99%